Implementation of the RSA Algorithm and the One Time Pad Algorithm for Text Message Security - Zulfahmi Indra; Rinjani Cyra Nabila (Formosa Journal of Science and Technology, 2023)
Securing data is one of the things that is very important to protect the contents of the data from parties who can harm it by destroying important data from the owner. This study applies two algorithms, namely the RSA algorithm and the One Time Pad algorithm. First use the RSA algorithm first with predetermined plaintext. After finishing working on the RSA algorithm, then continue working on the same plaintext as the One Time Pad algorithm. The results of the study show that the application of the RSA and One Tome Pad algorithms, the level of security of document files and text messages can be better maintained for the authenticity of the data. So that data leakage can be minimized.